Validation of a new serum granulocyte–macrophage colony-stimulating factor autoantibody testing kit. Issue 1 (27th January 2020) - Nakata, Koh; Sugi, Tatsuki; Kuroda, Keiko; Yoshizawa, Kazutaka; Takada, Toshinori; Tazawa, Ryushi; Ueda, Takahiro; Aoki, Ami; Abe, Mitsuhiro; Tatsumi, Koichiro; Eda, Ryosuke; Kondoh, Shotaro; et al.
Very recently, a modest but significant efficacy of granulocyte–macrophage colony-stimulating factor (GM-CSF) inhalation therapy for the treatment of mild to moderate autoimmune pulmonary alveolar proteinosis (aPAP) has been reported. As the ability to measure the level of GM-CSF autoantibody (GMAb) in the serum is required to decide the indication for this therapy, we developed a high-performance GMAb testing kit for clinical use. As the kit succeeded in reducing nonspecific IgG binding to the ELISA plate, the predictive performance shown in the training study to discriminate aPAP patients from healthy subjects was perfect, providing a cut-off value of 1.65 U·mL −1 in 78 patients with aPAP and 90 healthy subjects in an operator-blinded manner using logistic regression analysis. As in the validation study, serum samples from another 213 patients with aPAP were also blinded and evaluated in an operator-blinded manner against external 207 samples from patients with other types of PAP and patients exhibiting various ground-glass opacities on chest high-resolution computed tomography that require discrimination from PAP. The logistic regression analysis of these validation data sets revealed values of 97.6% and 100% for specificity and sensitivity, respectively. Thus, this new GMAb testing kit is reliable for the diagnosis of aPAP and differential diagnosis of other lung diseases. Using a newly developed ELISA kit, the cut-off value for serological diagnosis of autoimmune pulmonary alveolar proteinosis can be reset to 1.65 U/mL, which is externally validated against patients with conditions other than autoimmune PAP http://bit.ly/2LgFmKk